Рассказы. Повести. 1921-1934 - Платонов Андрей Платонович (1984)
Экземпляры: Селтинская районная библиотека (к/х) (20220809) / Инвентарный номер: 91541 / Авт.знак: П 37 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6